Insights from the everyday: implications of reframing the governance of water supply and demand from 'people' to 'practice'. (14th April 2015) - Browne, Alison L.
Abstract : While the emerging shift to 'people‐oriented' water management could be applauded, existing conceptual and methodological approaches limit understandings of consumer behavior and linked social, cultural, and infrastructural changes. Using the example of water demand throughout, 'people oriented' approaches are shown to deny complexity and homogenize ideas of the consumer and supply systems. The way in which this is enacted in current, dominant forms of water management and water demand is discussed. New and more responsive conceptual and methodological approaches are needed to address the existing and future uncertainties facing water sectors worldwide. 'Practice‐oriented' approaches are explored and shown to open up understandings of current diversities and complexities of demand and the patterns of these demands across populations. Such a conceptual and methodological reorientation reflects a need—potentially counter intuitively for those in the water industry—to let go of the focus on water and to instead focus on the services such resources provide in everyday lives and how these services could be more sustainably provisioned. Such an approach will assist in understanding current demand profiles, potentially improve the forecasting of future trajectories of change, and open up new routes for intervention to both water demand and water supply systems at various scales. Through the example of water demand, the implications of moving to a practice‐oriented approach for the governance of water systems more generally are considered. WIREs Water 2015, 2:415–424. doi: 10.1002/wat2.1084 This article is categorized under: Engineering Water > Planning Water Human Water > Water Governance